ANALISIS MEKANISME TRANSMISI KEBIJAKAN MONETER JALUR NILAI TUKAR DENGAN PENDEKATAN VECM PERIODE 2005:1-2012:12 - Nurobi Goldiman Wardianda; Dian Octaviani R (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This thesis discusses about analysis of transmission mechanism of monetary policy through exchange rate channel in Indonesia, during the period 2005:1 - 2012:12. By using variables such as PUAB Interest Rate, Exchange Rate, Total Export, National Income and Price lndex. The method's try to used in this thesis is a method of Vector Error Correction Models (VECM). This research aims to know the effectiveness of transmission mechanism of monetary policy through exchange rate channel within respect to see the influence of the operational targets (PUAB Interest Rate) to the intermediary target (Exchange Rate), as well as the final goals of monetary target (national income and price level). The results of this research show the transmission mechanism of monetary policy through exchange rate channel path deserves to be researched further, it is based on the significant value of the t-test, f-test, and Adj R2. Meanwhile, the results of the analysis of the